The influence of swimming performance in triathlon: implications for training and competition - Adriana Garcia Pacheco (Revista Brasileira de Cineantropometria e Desempenho Humano, 2012)
Triathlon is a sport that involves three different exercise modes, swimming, cycling and running, each of which contributes differently to the triathlete’s performance. The objective of the present study was to analyze the factors that determine performance in swimming and how this can be used in triathletes’ training and competitions. We searched articles on triathlon swimming using the following keywords in Portuguese: “triathlon,” “triatleta,” “performance na natação,” and their translations into English when necessary. Swimming is considered the most intense phase during a triathlon event. In short triathlon races, the intensity of this phase seems to be higher than the anaerobic threshold. The split time of this first phase seems to correlate positively with final time of the short races, which is not true for longer races. During the short and Olympic triathlon, the pacing strategy adopted at the swimming phase seems to directly influence the final outcome of the race. Thus, the planning of training loads within the three exercise modes of triathlon must take into consideration the distance and format of the races to achieve success.